Restoration of a vertical tooth fracture and a badly mutilated tooth using canal projection - Velmurugan N; Bhargavi N; Neelima Lakshmi; Kandaswamy D (Wolters Kluwer Medknow Publications, 2007)
Management of vertically fractured tooth or a perforation frequently poses problem during endodontic management. Such teeth often need a pre-endodontic restoration prior to initiation of root canal therapy to aid in the placement of rubber dam clamp. This paper describes a simple method of placement of a pre-endodontic restoration using the canal projection technique using hollow metallic needles as sleeves.